PM2.5 and associated ionic species in a sub-urban coastal area of Kuala Terengganu, Southern South China Sea (Malaysia) - Norhayati Mohd Tahir; Koh, Meikee; Suhaimi Suratman (Universiti Kebangsaan Malaysia, 2013)
PM2.5 mass concentration and associated water-soluble ionic species in a sub-urban coastal area of Kuala Terengganu, Malaysia were investigated intermittently from year 2006 to 2009. A total of 78 weekly PM2.5 samples were analyzed. The mass concentration of PM2.5 exhibited annual, seasonal and diurnal variations. Temporal distributions of rainfall, sporadic haze episodes and local air flow (sea breeze circulation) were factors controlling PM2.5 mass variations in the study area. Although the PM2.5 concentrations were increased during haze episodes in 2006 (August and October) and 2007 (October), their concentrations however, were still within the international guidelines. The average concentration of individual ions was in decreasing trend; SO42-> NH4+> K+> Na+> NO3-> Cl-> Ca2+. The concentrations of SO42- and NH4+ accounted for > 70% of the water-soluble aerosol mass. More than 80% of ionic species associated with PM2.5 are from non-marine sources. Major processes affecting the ionic composition of PM2.5 are biomass burning, crustal loading and sea spray. Air quality mitigation strategies should focus on anthropogenic activities emitting SO2, which promotes aerosol SO42- formation.